Differences on mood and arousal levels of collegiate volleyball athlete when using fast tempo music during warm up - Consuelo, Nicolo Brylle A. 1998-; Maghanoy, Mona Liza A. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
There were lots of studies that have been done to provide information about the effects of music on the performance of athletes but there is no research prior to these studies had examined the use of music particularly fast tempo music on the affective states of Filipino collegiate volleyball athletes. 43 male and female collegiate volleyball players are members of this study. Using Brunel's Mood Scale and The Checklist of Performance state, the arousal and the mood levels of athletes were measured. Mood and arousal levels were presented using SD and mean. Paired and independent t-tests were used through the SPSS software to analyze and compare the collected data. Profile of arousal and mood of volleyball athletes showed improvement on scores by getting desirable results when fast tempo music is present over no music. Paired t-test presented a significant difference in arousal and most of the mood subscales except, anger. Meanwhile, for the comparison of the effects of fast tempo music on male and female subjects, results in the independent t-test exhibited a significant difference in the arousal level while no significant difference on most of the subscales except fatigue. This study found out that fast tempo music allows Filipino collegiate volleyball athletes to become relaxed and calm and it was also discovered that male and female only differ in terms of lowering perceived effort when fast tempo music is applied during their warm up.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Athletes -- Psychology; Volleyball players -- Philippines -- Diliman (Quezon City).